Pemanfaatan Umbi Gadung Dan Umbi Uwi Sebagai Media Alternatif Substitusi Nutrient Agar (Na)Untuk Pertumbuhan Bakteri - Wachidah, Istianah (2016)
Abundance of natural resources that have been used as a substitute for bacterial growth media to encourage researchers to examine and make substitutions of alternative media Nutrient Agar is derived from gadung tuber and uwi tuber. Media usage of natural origin are concidered more economical. This study uses a Completely Randomized Design (CRD) with 2 factors. Factor 1 is a type is Escherichia coli and Staphylococcus aureus. Factor 2 is the type of media that is gadung tuber, uwi tuber,and Nutrient Agar (NA) is a media control. The second test bacteria inoculated by means of a spread plate and incubated for 24-48 hours at 37oC. The parameters measured were the number population and size of the of bacterial colonies. Total populous, either Esherichia coli or Staphylococcus aureus is the gadung tuber media with the results of Too much Too Count (TMTC) which means that the population of bacteria very much. Total population of Escherichia coli in media uwi tuber was 2,3×109 CFU/ml and the media NA 3,6×109 CFU/ml. Total population of Staphylococcus aureus in uwi tuber was 2,3×109 CFU/ml and the media NA is 5,5×109 CFU/ml. Best bacterial colony size (large easily and observed) are on NA media, while in between the two media tuber bacterial colonies best (easily observed and large) is the tuber uwi media. The results showed that the alternatif media of gadung tuber and uwi tuber can be used as a substitute NA media for bacterial growth. Keywords : gadung tuber, uwi tuber, nutrient agar, bacteria, bacterial growth media.